Salt clogging during supercritical CO2 injection into a downscaled borehole model. (July 2019) - Berntsen, Andreas; Todorovic, Jelena; Raphaug, Martin; Torsæter, Malin; Chavez Panduro, Elvia Anabela; Gawel, Kamila
Graphical abstract: Highlights: CO2 injection into saline aquifer is often associated with salt precipitation. Brine backflow plays an important role in salt-induced wellbore clogging. Drying and precipitation regimes are governed by fluids distribution. Abstract: Injection of CO2 into saline storage aquifers is often accompanied by drying of the formation water and salt precipitation. Subsequent salt clogging of a well bore and the near wellbore rock matrix may lead to injectivity impairment. In this paper we present medium-scale experiments on salt precipitation in the near-well region during a dry CO2 injection. In an effort to better simulate the geometry and the flow conditions in the field situation our purpose-designed experimental setup enables (1) realistic radial geometry of CO2 flow, and (2) opened boundary conditions for brine inflow allowing capillary and diffusive flux of brine components from and to practically infinite source of formation water. During the course of injection, no significant pressure build-up was observed across the rock specimen, indicating that permeable flow paths were not completely clogged. Post-test analysis of the specimen included X-ray computed tomography, powder X-ray diffraction and scanning electron microscopy in order to quantify fluid saturation, brine salinity and halite precipitation. The analysis provided indication of the most probable flow patterns of supercritical CO2 and CO2 rich brine in the system. The resulting drying and precipitation is discussed in light of the different drying regimes created under the present flow conditions.